A comparative study of the modification of black glutinous rice starch using acid hydrolysis-autoclaving cooling and octenyl succinic anhydride - Mustofa, Akhmad; Anam, Choiroel; Praseptiangga, Danar; Sutarno (Asia-Pacific Journal of Science and Technology, 2025)
Starch modification can alter its characteristics to align with industrial requirements. Modified starch can be developed as an alternative food product with the desired properties or characteristics. Modifying black glutinous rice starch using acid hydrolysis-autoclaving cooling (AH-AC) and esterification using octenyl succinic anhydride (OSA) represents a novel approach. This study examines the characteristics of black glutinous rice starch modified through the AH-AC method and esterification using OSA. In addition to amylose, amylopectin, dietary fibre, antioxidant activity and anthocyanin content, the modified starch was also examined for its swelling power and pasting properties, degree of substitution for OSA starch, and visual appearance. The findings indicate that starch modification altered the content of amylose, amylopectin and total-resistant starch. Additionally, the swelling power, peak viscosity (PV) and trough viscosity (TV) of OSA-modified starch were superior to those of the AH-AC version. The electron micrographs of the structure of the OSA and AH-AC-modified starches also differed. Scanning electron microscopy (SEM) of the modified starches revealed an uneven surface, wavy and nonpolygonal shape, and altered size.